Differential transformation efficiency of Japonicarice varieties developed in northern China - Li,Dan (2015)
The production of japonica rice in northern China plays an important role in food security for the world. Agrobacterium-mediated gene transfer is becoming a powerful approach to generate germplasm and develop varieties. However, the transgenic efficiency of the japonica rice varieties in northern China has been completely unknown, which obstructs the development of transgenic breeding and the exploration of gene functions. In this study, the transgenic efficiencies of six japonica rice varieties developed in northern China are evaluated. The rates of primary and secondary callus induction of the varieties are similar. However, transgenic efficiency and the regeneration ability of the varieties are greatly different. The results have established a platform for transformation of the rice varieties and proposed a suitable variety, SN9816, for gene transfer. SN9816 can be applied as an elite germplasm for transgenic breeding and basic research of molecular biology in northern China or an area in the same latitude.